Children's perspectives on their Young Lives: report on methods for sub-studies, Peru Pilot, April 2006 - Johnston, J (Young Lives, 2006)
Alongside the Young Lives full-cohort surveys carried out every four years, Young Lives sub-studies are to be carried out to investigate pre-identified themes in greater depth across all four countries. These will be carried out by sub-sampling sites and index children within the main sample frame. This pilot project aimed to implement and develop methods for these sub-studies, especially the use of semi-structured methods with groups of children to gather both quantitative and qualitative data. The methods were identified through an extensive review of literature detailing participatory, quantitative and qualitative work with children and adults and developed for the specific age groups and research questions. Methods were chosen and evaluated using the following criteria: (1) Semi-structured – to ensure that the core themes can be studied consistently through an agreed set of methods, to allow for inter-country comparability; (2) Applicable in diverse settings – these methods will need to be implemented in very diverse settings across all four countries, including by fieldworkers with very variable research training, orientation and experience; (3) Flexibility – to allow children to identify themes and issues that are important to them, including collecting detailed data from selected group discussions and individual interviews; (4) Efficient recording and analysis of structured and semi-structured data – since coding full focus group transcripts can be highly costly in terms of time and money; and (5) Adaptability – since there is a great variation in educational levels, cultures, and preferred methods of communicating amongst children within the Young Lives project. The research investigated four inter-related themes: time use, wellbeing, poverty and social worlds. Four groups (31 children) in an urban site and three (21 children) in a rural site were identified for the research. The children in one group in each site were eight to nine years old, while the others were 11-12 years old. A session for each of the themes was designed and conducted with each of the older groups, while a sub-set of these methods were used with the younger groups. A number of individual interviews were also conducted in different sessions. For each session, this report outlines methods that can be kept, adapted, added or removed in planning for the sub-studies with children. It also outlines modifications for making the methods more appropriate for use with non-literate or younger children and for contexts where more unstructured methods are feasible. These changes need to be worked into future protocols for sub-studies, which then need to be piloted. These protocols should be viewed as a ‘tool box’ for the research, with a core of agreed methods, but scope for teams to make some adaptations and extensions as appropriate.